Hillbillies, Genetic Pathology, and White Ignorance: Repackaging the Culture of Poverty within Color-blindness. Issue 4 (October 2019) - Byrd, W. Carson
Leading up to and since the 2016 presidential election, a recurring theme focusing on poor whites' role in carrying the Republican nominee to victory gained further credence with the popularity and wide readership of J. D. Vance's Hillbilly Elegy . Peddling stereotypes of Appalachia as a white dystopia with a backward mountain culture, the memoir seemingly turned the use of culture-of-poverty arguments on whites themselves. Through an examination of Hillbilly Elegy, its arguments, and its context, the author offers an initial answer to the question of how a memoir perpetuating culture-of-poverty arguments resonates across the political spectrum among whites when a segment of their group is the target of such arguments. The successful repackaging of cultural pathology within color-blindness allows a subversive use of genetic determinism and racial essentialism, selling inequality as a natural phenomenon embedded within inferior bodies. Building on stereotypes of poor white Appalachians as unevolved and "not quite white, " Vance's memoir provides a cautionary tale of how narratives conforming to the reproductive practices of white ignorance gain popularity through absolving whiteness from complicity in racism and systemic inequalities, while also performing boundary work for whiteness as an identity and structure.